Effect of Hydrothermal reaction times and temperature-dependent Spherical like NiCo2O4 nanoparticles for supercapacitor application. (10th November 2022) - Priya, M.; Vasantharani, P.; Sivakumar, G.
ABSTRACT: The effects of reaction times and temperatures on the electrochemical capacitance characteristics of NiCo2 O4 nanoparticles (NPs) are investigated. The hydrothermal reaction temperatures and times play critical parts in the creation of unique hierarchical NCO based on morphological evolution in this work. The calcination temperature 400 °C was fixed using TG-DTA study. The crystal structure and phase identification is investigated from XRD analysis. FTIR peaks in the region of 700-500 cm −1 confirmed the presence of the Ni-O and Co-O bond. The spherical-like nanostructure NiCo2 O4 particles are visualized from SEM, HR-SEM and HR-TEM analyses. From the EDS spectra, the atomic percentage composition of the elements namely, Ni, Co and O were observed. The optimized sample was subjected to a VSM and CV analyses, which revealed that it is superparamagnetic nature (Ms = 4.8298 emu/g) and Pseudocapacitive behaviour with highest capacitance value of 534 Fg −1 with the lower scan rate of 10 mVs −1 .